Guidelines for the preparation of expatriates on international assignments in South African multinational enterprises - De Wit, P.W.C. (Pieter Willem Combrink), 1947- (University of Pretoria, 2013)
Thesis (DComm (Business Management))--University of Pretoria, 2005.